Behavioral pattern separation and cognitive flexibility are enhanced in a mouse model of increased lateral entorhinal cortex-dentate gyrus circuit activity - Yun, Sanghee; Soler, Ivan; Tran, Fionya H.; Haas, Harley A.; Shi, Raymon; Bancroft, Grace L.; Suarez, Maiko; de Santis, Christopher R.; Reynolds, Ryan P.; Eisch, Amelia J. (Frontiers in Behavioral Neuroscience, 2023)
Behavioral pattern separation and cognitive flexibility are essential cognitive abilities which are disrupted in many brain disorders. Better understanding of the neural circuitry involved in these abilities will open paths to treatment. In humans and mice, discrimination and adaptation rely on integrity of the hippocampal dentate gyrus (DG) which receives glutamatergic input from the entorhinal cortex (EC), including the lateral EC (LEC). Inducible increase of EC-DG circuit activity improves hippocampal-dependent learning and increases DG neurogenesis. We asked if the activity of LEC fan cells that directly project to the DG (LEC➝DG neurons) regulates the complex hippocampal-dependent abilities of pattern separation or cognitive flexibility. C57BL6/J male mice received bilateral LEC infusions of a virus expressing shRNA TRIP8b, an auxiliary protein of an HCN channel, or a control virus (SCR shRNA). Prior work shows four-weeks post-surgery TRIP8b mice have more DG neurogenesis and greater activity of LEC➝DG neurons vs. SCR shRNA mice. Here, four-weeks post-surgery mice underwent testing for behavioral pattern separation and reversal learning (touchscreen-based Location Discrimination Reversal [LDR]) and innate fear of open spaces (elevated plus maze [EPM]) followed by quantification of new DG neurons (doublecortin-immunoreactive cells [DCX+] cells). There was no effect of treatment (SCR shRNA vs. TRIP8b) on performance during touchscreen or LDR training or the first days of LDR testing. However, in the last days of LDR testing, TRIP8b shRNA mice had improved pattern separation (reached first reversal more quickly, were more accurate) vs. SCR shRNA mice, specifically when load on pattern separation was high (“small separation” of lit squares). Also in the last LDR testing days, TRIP8b shRNA mice were more cognitively flexible (achieved more reversals) vs. SCR shRNA mice. Supporting a specific influence on cognition, SCR shRNA and TRIP8b shRNA mice did not differ in distance traveled or time spent in closed EPM arms. Supporting an inducible increase in LEC-DG activity, DG neurogenesis was increased. This work advances fundamental neuroscience knowledge relevant to two cognitive functions critical for adaptation and survival and suggests the activity of LEC→DG neurons merits exploration as a therapeutic target to normalize dysfunctional DG behavioral output.